A comparative study of TVET in 5 African Countries with a specific focus on TVET Teacher Education - Papier, Joy (2017)
This article describes a five country (Cameroun, Egypt, Ghana, South Africa, Tanzania) study of ‘TVET Teacher Education in Africa’ that was commissioned in terms of an EU-South African collaboration in 2013. While the focus was on vocational teacher education, the contextual realities of each country‘s vocational systems was studied as this would impact on every aspect of vocational teacher development, for instance, what teachers would have to teach, who the students might be, how students would be expected to learn, available funding for Vocational Education and so on. Comparisons were therefore made over a range of elements that included the systems in place for vocational training, systems of vocational teacher education, and the modalities for training of VET teachers.
KerkoCite.ItemAlsoKnownAs: 2129771:8J6PBLVZ 2317526:6TNBGFXK
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; CLL:en; _C:Denmark DNK; _C:Egypt EGY; _C:Finland FIN; _C:Ghana GHA; _C:Ireland IRL; _C:Netherlands NLD; _C:South Africa ZAF; _C:Sweden SWE; _C:Tanzania TZA; __C:filed:1; __C:scheme:1; publicImportV1; ⛔ No DOI found